Empirical evidence against placebo controls. Issue 10 (9th August 2017) - Batra, Sadhvi; Howick, Jeremy
Abstract : The revised Declaration of Helsinki allows placebo-controlled trials to be used even when there is an established therapy, provided there are adequate 'methodological' reasons for doing so. This seems to violate the principle of beneficence: where there is an established therapy, physicians treating patients with a placebo are withholding a known effective therapy. Because of this problem, we hypothesised that clinical researchers may be unwilling to risk violating the principle of beneficence and employ placebo-controlled trials in cases where there is an established therapy. In this paper, we began to investigate this hypothesis. After summarising the arguments for and against using placebo controls in clinical practice, we exploredthe extent to which placebo-controlled trials are used in cases where there is an established therapy. To do this, we conducted as systematic search for all placebo-controlled trials published in 2015 in the five highest impact general medical journals. We identified 70 placebo-controlled trials. Of these, 66 were for indications where there was no established effective therapy. Only four used a placebo control in spite of there being an available effective therapy. The infrequent use of placebo controlled trials where established therapy exists highlights a seeming discrepancy between what the Declaration of Helsinki allows and what clinical investigators believe to be ethically acceptable. The evidence presented in this paper suggests that the Declaration of Helsinki be reconsidered, and perhaps revised, in light of actual practice.